K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 3 2021

a) Ta có: f(2)-f(-1)=(m-1).2-[(m-1).(-1)]=7

<=> 2m-2+m-1=7 <=> 3m=10 => m=10/3

b) m=5 => f(x)=4x

 => f(3-2x)=4(3-2x)=20 <=> 3-2x=5 => 2x=-2 => x=-1

28 tháng 3 2017

a) Ta có: f(2)-f(-1)=(m-1).2-[(m-1).(-1)]=7

<=> 2m-2+m-1=7 <=> 3m=10 => m=10/3

b) m=5 => f(x)=4x

 => f(3-2x)=4(3-2x)=20 <=> 3-2x=5 => 2x=-2 => x=-1

28 tháng 3 2017

a,f(-1)=3

=>(m-1)x=3

=>(m-1)3=3

=>3m-3=3

=>3m=6

=>m=2

b,Với m=2

=>f(3)=(2-1)3

         =3

Vậy f(3)=3

24 tháng 12 2020

Ta có : \(f\left(x\right)=2x+3m\)hay \(f\left(-2\right)=2\left(-2\right)+3m=-1\)

\(\Leftrightarrow-4+3m=-1\Leftrightarrow3m=3\Leftrightarrow m=1\)

Vậy m = 1 

4 tháng 3 2016

y=f(m2)=1-5.m2=-19

          =5m2=20

          =m2=4

=> m=2 hoac -2